Long‐term follow‐up of Cladribine, high‐dose Cytarabine, and Idarubicin as salvage treatment for relapsed acute myeloid leukemia and literature review. (10th March 2020) - Mayer, Karin; Hahn‐Ast, Corinna; Schwab, Katjana; Schmidt‐Wolf, Ingo G. H.; Brossart, Peter; Glasmacher, Axel; von Lilienfeld‐Toal, Marie
Abstract: Purpose: Outcome for relapsed acute myeloid leukemia (AML) is poor. Cladribine has activity in AML, and an enhancing effect on other cytostatic drugs thus may help overcome resistance. Here, we present the final analysis of our phase II trial evaluating safety and efficacy of cladribine, cytarabine, and idarubicin (CAI) in relapsed AML. Methods: Patients with relapsed AML after at least 6 months remission received two courses of CAI. After 9 patients, prolonged neutropenia prompted protocol change (omission of idarubicin in 2nd course and dose‐reduction of cytarabine). Primary endpoints were remission rate and safety. Results: Twenty patients received treatment, fourteen one, and six two courses CAI/CA. After first course, complete remission (CR/CRi) was achieved in 60%. Most frequent toxicity was infection. Median OS was 8.8 months in all patients and 21.1 months in those with CR. Nine patients (48%) proceeded to allogeneic stem cell transplantation (allo‐SCT), four of those are still alive and in CR, accounting for a 5‐year survival rate of 55% of transplanted patients. Conclusion: Cladribine, cytarabine, and idarubicin in relapsed AML is feasible and induces good response rates. As expected, infections are the most important complication. However, combined with allo‐SCT, long‐term survival can be achieved in a substantial number of patients.